Nucleoside analog GS‐441524: pharmacokinetics in different species, safety, and potential effectiveness against Covid‐19. Issue 2 (9th April 2022) - Rasmussen, Henrik Berg; Thomsen, Ragnar; Hansen, Peter Riis
Abstract: GS‐441524, the parent nucleoside of remdesivir, has been proposed to be effective against Covid‐19 based on in vitro studies and studies in animals. However, randomized clinical trials of the agent to treat Covid‐19 have not been conducted. Here, we evaluated GS‐441524 for Covid‐19 treatment based on studies reporting pharmacokinetic parameters of the agent in mice, rats, cats, dogs, monkeys, and the single individual in the first‐in‐human trial supplemented with information about its activity against severe acute respiratory syndrome coronavirus 2 and safety. A dosing interval of 8 h was considered clinically relevant and used to calculate steady‐state plasma concentrations of GS‐441524. These ranged from 0.27 to 234.41 μM, reflecting differences in species, doses, and administration routes. Fifty percent maximal inhibitory concentrations of GS‐441524 against severe acute respiratory syndrome coronavirus 2 ranged from 0.08 μM to above 10 μM with a median of 0.87 μM whereas concentrations required to produce 90% of the maximal inhibition of the virus varied from 0.18 µM to more than 20 µM with a median of 1.42 µM in the collected data. Most of these concentrations were substantially lower than the calculated steady‐state plasma concentrations of the agent. Plasma exposures to orally administered GS‐441524, calculated after normalization of doses, were larger for dogs, mice, and rats than cynomolgus monkeys and humans, probably reflecting interspecies differences in oral uptake with reported oral bioavailabilities below 8.0% in cynomolgus monkeys and values as high as 92% in dogs. Reported oral bioavailabilities in rodents ranged from 12% to 57%. Using different presumptions, we estimated human oral bioavailability of GS‐441524 at 13% and 20%. Importantly, doses of GS‐441524 lower than the 13 mg/kg dose used in the first‐in‐human trial may be effective against Covid‐19. Also, GS‐441524 appears to be well‐tolerated. In conclusion, GS‐441524 has potential for oral treatment of Covid‐19.